Evaluation of plasma microsampling for dried plasma spots (DPS) in quantitative LC-MS/MS bioanalysis using ritonavir as a model compound - Li, Wenkui; Doherty, John; Favara, Sarah; Breen, Christopher; Flarakos, Jimmy; Tse, Francis L.S. (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2015)
•Plasma microsampling for dried plasma spots (DPS) was evaluated for the first time using ritonavir.•An LC-MS/MS method was developed and validated for the analysis of ritonavir in dog DPS.•The results of DPS via plasma microsampling correlated well with those via standard pipetting.•Both sets of DPS results correlated well with those measured in wet plasma.•Plasma microsampling for DPS can serve as an alternative to wet plasma in in vivo studies. Quantitative bioanalysis of dried plasma spots (DPS) is not subject to the impact of hematocrit and sample non-homogeneity that are often encountered in dried blood spot (DBS) assay. In the present report, an evaluation of plasma microsampling for DPS has been conducted for the first time using ritonavir as a model compound orally administered to dogs. For this evaluation, an LC-MS/MS method was developed and validated according to the current health authorities’ guidance and industry practice for the analysis of ritonavir in DPS samples. The measured ritonavir concentrations in the DPS samples prepared using SAFE-TEC devices and directly from the conventional wet plasma using standard pipette were compared with each other and against those of conventional wet plasma. Both DPS results correlated well with each other and were comparable to those of the wet plasma. Good incurred sample reanalysis results were obtained for the two sets of DPS samples and wet plasma as well. The current plasma microsampling for DPS can serve as an alternative to DPS sampling via standard pipetting and wet plasma in in vivo studies.